PEMETAAN FAKTOR RISIKO LINGKUNGAN LEPTOSPIROSIS DAN PENENTUAN ZONA TINGKAT KERAWANAN LEPTOSPIROSIS DI KABUPATEN DEMAK MENGGUNAKAN REMOTE SENSING IMAGE - Siti Rahayu; Mateus Sakundarno Adi; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Leptosiprosis is a zoonotic disease caused by Leptospira bacteria and transmitted to human by contact through contaminated animal urine and environment contaminated of Leptospirosis. Demak District is an endemic area of Leptospirosis bacteria. The prevalence of Leptospirosis case has increased in the past 2 years. The aim of this research is to map environmental risk factor of Leptospirosis and to determine Leptospirosis vulnerable zone. This research is analyzed in a descriptive using cross sectional design. 42 Leptospirosis cases are mapped with GPS. Leptospirosis case was overlaid with remote sensing (Quickbird image) by using ArcView program. Then interpreted by Spasial Feature and Spasial Analyses.Leptospirosis cases in 2014-2015 was spread out and a bit gouped in Demak Sub District area. More cases are found in male (61,9%), productive age 21-50 years (59,3%), farmer (40,4%). Spasial analyses shows that the leptospirosis cases take place at low plain <47 masl (100%), rainfall ≥220 mm/month (64,7%), clay soil (100%), buffer river <50 m (71,4%), presence of rat (100%), wastewater disposal (100%), waste disposal facilities (97,7%), flood’s profile (28,6%), rob’s profile (7,1%), vegetation (59,5%). Leptospirosis high risk zone is 37.801,8 ha (41,32%), risk zone is 43.570,23 ha (48,55%), and low risk zone is 9.090,96 ha (10,13%). Densely populated housing, environment condition, and presence of rat with contact of puddle are risk factors of Leptospirosis cases in Demak District.